Alcoholism in a General Hospital - Bueno, Edgar (1966)
It has made a study of the incidence of alcoholism in the Police Hospital , through a period of 20 years ( 1944-1964 ) , reviewing medical records of 7819 Psychiatrist Department . There were found 278 individuals (3.5 percent) that corresponded to the diagnosis of the different forms of alcoholism. Age at onset as social drinkers , the type of beverage ingested and frequency of intake was considered ; appreciated that 68.3 percent of subjects hcbíon started drinking before age 25. ; 70.6 percent drank daily admission to hospital • ... and 74.1 percent ate drinks with high alcohol concentration. Frequency was studied at different stages of the addiction and found to be 85.5 percent were alcoholómanos , social drinkers and 6.8 percent symptomatic drinkers 5.4 percent . Presentation of the different classical clinical forms was also investigated , highlighting the high frequency of delirium tremens with 12.9 percent and pathological intoxication (12.9 percent). In more than 40 percent of cases alcoholism was a symptom of other psychological disturbance. Mental disorders that most frequently associated with alcoholism were personality disorders ( 32 percent) , chronic brain syndromes (11.5 percent) , depressive reactions (6.8 percent). It was found that the association with no organic brain cuaáros was low. Men predominated greatly over women. There were high numbers of alcoholics among graduates of the police force and in individuals who had served in that body for 10 to 14 consecutive years. High levels of alcohol among married subjects and those with little schooling was also verified . The figures obtained suggest that the alcoholic habit develops between those living on the coast than in those who live in the mountains or jungle . Alcoholism among members of the armed and auxiliary forces may lead to the commission of serious criminal acts, what is required to establish preventive measures , preventing the entry of individuals with severe to those institutions psychological disorders, and early detecting drinkers excessive , in order to treat and get the maximum possible rehabilitation. In this series a method of holistic treatment , which consisted of the association of individual psychotherapy and group intervention Alcoholics Anonymous, psychoactive drug use , in its amended linoterapia , aversion therapy with disulfiram and recreational , sports and labor was employed.